Rasisme dalam Iklan âDjarum Supersoccerâ dan âGudang Garam Intersportâ (Sebuah Analisis Semiotika dan Resepsi Audiens) - , Filosa Gita Sukmono, Dr. Budiawan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to see how the articulation of racism that was shown in the football-themed cigarette advertisements. This study aims to see how the articulation of racism that was shown in the football-themed cigarette advertisements. Ads that had been analyzed were football-themed cigarette advertisement of Djarum Supersoccer and Gudang Garam Intersport which had been aired on television throughout 2010, especially during the World Cup event. In order to find out the articulation of racism which displayed in both of those advertisements, the researcher had combined the text research studies and audience research studies. The researcher combined the text research and audience research because researcher wanted to see the results of the construction of meaning through the signs inside football-themed cigarette advertisement of Gudang Garam Inter Sport and Djarum Super Soccer which completed with how the audience reception thinks about those two ads. The result of semiotics text analysis shows that both of Djarum Super Soccer and Gudang Garam Intersport have equally showed the articulation of racism. Djarum Super Soccer advert in African Animals version shows the articulation of racism in the form of animal symbols that are identical to the Africa Continent. Furthermore, Gudang Garam Intersport shows the articulation of racism in the form of White People superiority against Blacks. On the other side, audience reception method by using Focus Group Discussion shows the fact that viewers think critically and suspiciously on both of those advertisements. Besides even one of the participants had the same viewpoint with researchers in viewing advertisements although the audience didn't use semiotics to see and interpret those ads. The conclusion of the study shows that the articulation of racism in advertisement of Gudang Garam Inter Sport and Djarum Super Soccer has become the myth that the animal is identical to African football players. The Blacks are identical to the violent, brutal, and unfair play. This articulation of racism has affected the audienceâs view point toward a certain race especially Blacks.